Speaking Competence of University Students - Wayan Maba (International Journal of Social Science, 2022)
Speaking is an important language skill to be developed continually. This language skill enables students to communicate in English appropriately. This study aims at analysing students’ speaking competence to attain explicit knowledge concerning students’ speaking ability. This study used an ex post facto research design. The data were collected by conducting a speaking assessment of the selected samples, and the data were descriptively analysed. This study found that students speaking competence were sufficient. Some students still needed help expressing their ideas using correct grammar and appropriate language functions. Therefore, the study implies that the students' speaking competence needs to be developed progressively in the classroom to attain a higher level of competency